2022
DOI: 10.3389/fmicb.2022.994421
|View full text |Cite
|
Sign up to set email alerts
|

Identification of essential genes in Mycobacterium avium subsp. paratuberculosis genome for persistence in dairy calves

Abstract: To cause disease Mycobacterium avium subsp. paratuberculosis needs to enter mammalian cells, arrest phagosomal maturation and manipulate the host immune system. The genetic basis of the bacterial capacity to achieve these outcomes remains largely unknown. Identifying these genes would allow us to gain a deeper understanding of MAP’s pathogenesis and potentially develop a live attenuated Johne’s disease vaccine by knocking out these genes. MAP genes demonstrated to be essential for colonization in the natural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…paratuberculosis and their efficacy to induce cell-mediated immune responses by a comparative approach in mouse and natural host calf models. A previous study identified genes necessary for MAP survival in dairy calves and permitted us to select a gene to knockout that is essential for MAP survival in vivo (MAP1643, IcL ) or one which is required for intracellular growth (MAP1531c, BacA ) ( EshraghiSamani et al., 2022 ). The results of the current study confirmed the attenuation of these mutants in calves and indicated that disruption of these genes affect MAP's intracellular survival without affecting its immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…paratuberculosis and their efficacy to induce cell-mediated immune responses by a comparative approach in mouse and natural host calf models. A previous study identified genes necessary for MAP survival in dairy calves and permitted us to select a gene to knockout that is essential for MAP survival in vivo (MAP1643, IcL ) or one which is required for intracellular growth (MAP1531c, BacA ) ( EshraghiSamani et al., 2022 ). The results of the current study confirmed the attenuation of these mutants in calves and indicated that disruption of these genes affect MAP's intracellular survival without affecting its immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type is able to advert immune system by having all these properties and this will delay the activation of macrophages and the downstream signaling pathways ( Arsenault et al., 2014 )and delay the proinflammatory responses. In addition, the deletion of BacA has been found to impair MAP growth in vivo ( EshraghiSamani et al., 2022 ), these might suggest that Δ BacA is not over-attenuated to get cleared before inducing immune responses, and it is not under-attenuated to persist in tissue and maintain a chronic infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the larger Mac and Map genome dataset in this study identified four copies of the PE-PGRS gene in Map Type B, Mah and M. chimaera and two copies in Type C, Type S, Maa and M. intracellular. There are four PPE proteins (PPE4, PPE65, PPE25 and PPE26), all members of the ESX-5 and ESX-3 systems that are essential for virulence in Mycobacteria [ 33 ]. The PPE4 protein was found in only two out of the 52 Type S strains.…”
Section: Discussionmentioning
confidence: 99%
“…The BacA gene is essential for the optimal growth of Mycobacterium avium subsp. paratuberculosis (MAP) in calf tissue (20,21), and it is involved in the import of hydrophilic compounds such as vitamin B12 and iron metabolism. Mycobacterium tuberculosis mutant of BacA indicated diminished capacity to maintain a chronic infection (22).…”
Section: Introductionmentioning
confidence: 99%